Greenhouse microclimate real-time monitoring based on wireless sensor network and gis - Postolache, Octavian (2018)
Trabalho apresentado em XX IMEKO World Congress Metrology for Green Growth, 9-14 setembro de 2012, Busan, Coreia do Sul